Bringing Technology in the English Classrooms - Bhetuwal, Kamali Kanta (KMC Research Journal, 2019)
Technology is one of the crucial and inevitable parts needed in twenty first century of the educational world. It is very important and challenging aspect in language education which is discussed below in this article. Human behavior is affected by technology is also highlighted in this article. How the language instructors bring effective and essential technological tools in English classrooms to enhance and promote learning of the students. Technologies provide a pedagogical basis for understanding how students learn and some of the approaches to teaching with technology use the best technological tools, and appropriate type of instruction to enhance learning under Bloom’s taxonomy are included. So, the technology offers for education and learning. Technology is now very essential in education, not only to the learners but to the instructor and school manager as well. Instructors must be on the edge of updating themselves in the integration of technology in teaching. Research must be conducted apart from what has been published. More articles are needed to publish to add more learning to the students and teachers to enhance in their learning through the incredible support of technology. Students should be provided ample opportunity through it to save their possible future that only can open the door of success in their learning.